Kehidupan Para Pelajar-Perantau Batak di Batavia (1907-1945) - Andrew, Teguh Vicky (Jurnal Sejarah, 2018)
This research aims to elaborate the role of western education which in a short time can transform Batak isolated and left behind-ethnic groups into the modern urban society. Therefore, in particular the discussion of this study was directed to the lives of Batak migrant at the beginning of the 20th century to the end of World War II. In that period, they were trying to shape the image as educated group for the purpose of dismantle negative stereotypes which labeled to Batak society and align themselves with students from other ethnic group who are fully formed new layer of urban society that actively involved in the heart of national movement. Through the establishment of various ethnic-based organizations, Batak students do not just create the medium of activism to struggling the strategic interests, but also asserted cultural identity which had been deliberately hidden. Nevertheless at the same time, as shown in this research, these tendencies results the dissolution of solidarity among Batak students who has been built before and immediately replaced by the creation of more specific and tight criteria which lead to the denial their cultural identity because it is considered to have been dominated by Batak-Toba ethnic group. Keywords : Urban Society, Educated Group, Students Activity, National Movement, Cultural Identity.